(untitled) (The Review of Diabetic Studies, 2024)
Background: Nasopharyngeal carcinoma (NPC) is a malignancy with a distinct epidemiology, showing a high prevalence in East and Southeast Asia. Its etiology is multifactorial, involving Epstein-Barr virus (EBV) infection, genetic susceptibility, and environmental factors like consumption of preserved foods. The deep anatomical location of the nasopharynx and the frequent presentation at advanced stages complicate management. Aim: This review aims to consolidate current knowledge on the multidisciplinary management of NPC patients undergoing chemo-radiotherapy, encompassing epidemiology, pathophysiology, diagnosis, staging, treatment protocols, and the essential role of integrated healthcare teams. Methods: A comprehensive review of the scientific literature was conducted, synthesizing information on NPC’s anatomical basis, histopathological classification (WHO types 1-3), diagnostic evaluation (including endoscopy, CT, MRI, and PET-CT imaging), and evidence-based treatment strategies. The central role of concurrent chemoradiation, primarily with cisplatin-based regimens and intensity-modulated radiation therapy (IMRT), is detailed. Results: Treatment for locoregionally advanced NPC (Stages II-IV) is primarily nonsurgical, relying on concurrent chemoradiation, which significantly improves survival. IMRT allows precise targeting, improving local control while reducing toxicity. Induction or adjuvant chemotherapy is used in advanced cases. Prognosis is stage-dependent, with 5-year survival rates ranging from approximately 82% for Stage I to 49% for Stage IV. Care is complicated by acute and late treatment-related toxicities, including xerostomia, dysphagia, and hearing loss. Conclusion: The management of NPC necessitates a complex, protocol-driven approach centered on chemo-radiotherapy. Optimal patient outcomes are achieved through a coordinated, multidisciplinary team strategy that integrates precise staging, advanced radiation techniques, systemic therapy, and comprehensive supportive care to manage treatment sequelae and ensure long-term surveillance.